Impedance matching for curl and truncated spiral antennas above the ground plane - Hirose, Kazuhide; Ito, Naonoshin; Nakano, Hisamatsu (Journal of engineering (Stevenage, England), 2023)
Curl and truncated spiral antennas are studied for input impedance matching a coaxial line. Each antenna is located at quarter wavelengths above the ground plane and analyzed using the moment method. It is found that the curl antenna shows a voltage standing wave ratio (VSWR) of less than two in a 3‐dB axial ratio bandwidth of 30% using a crank feedline with an unbalanced feed. It is also found that the spiral antenna has an axial ratio bandwidth of 24%, where the VSWR remains less than two using parallel feedlines with a quasi‐balanced feed. Curl and truncated spiral antennas are studied for input impedance matching a coaxial line. Each antenna is located at quarter wavelengths above the ground plane and analyzed using the moment method.